Determining friction properties of ABS plastic in contact with loamy soil - S. A. Kvas; A. S. Zolotarev (Сельскохозяйственные машины и технологии, 2024)
The paper explores the feasibility of substituting steel working bodies with polymer ones in soil-cultivating units. (Research purpose) The research aims to investigate how the friction parameters of acrylonitrile butadiene styrene (ABS plastic) are affected by variations in absolute soil moisture and speed of the unit during the interaction of its working body with loamy soil. (Materials and methods) A laboratory unit was developed to examine the friction characteristics of the polymer in contact with loamy soil. The study measures the friction and adhesion properties by altering the absolute moisture of loamy soil. (Results and discussion) Graphs were constructed to illustrate the relationship between of the friction parameters of acrylonitrile butadiene styrene (ABS plastic) on absolute soil moisture. It was determined that at absolute soil moistures of 18, 20 and 26 percent, the friction coefficients of acrylonitrile butadiene styrene are 0.45, 0.5 and 0.6, respectively. The adhesion values were recorded at 100, 145 and 700 pascals for absolute soil moistures of 18, 20 and 28 percent, respectively. A decrease in both friction and adhesion was observed when the soil moisture reached between 26% and 28%. (Conclusions) The friction properties of acrylonitrile butadiene styrene (ABS plastic) are lower than those of steel, yet significantly higher than those of fluoroplastic. Further research in this area is expected to significantly increase the effi ciency of selecting materials for the manufacturing of working parts in soil-cultivating units, while also reducing energy costs.